2018
DOI: 10.1029/2018tc005151
|View full text |Cite
|
Sign up to set email alerts
|

The Seismic Potential in the Seismic Gap Between the Wenchuan and Lushan Earthquakes Revealed by the Joint Inversion of Receiver Functions and Ambient Noise Data

Abstract: Based on a dense seismic array deployed to monitor the seismic gap between the Wenchuan and Lushan earthquakes, a joint inversion of dispersion curves and receiver functions yielded a fine velocity structure in this region with the highest resolution of approximately 20 km. The results show that the upper crust of the Songpan‐Ganzi terrane overthrusted onto the basement of the Sichuan Basin, indicating that the crustal shortening model may be the major mechanism that accounts for the growth of the Longmenshan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…According to the sensitivity kernel curve shown in Figure S5, the results of T = 20, 40, and 60 s are mostly sensitive to the structures at depth ranges of approximately 25, 60, and 90 km, respectively. The isotropic velocity maps of the southeastern Tibetan Plateau are consistent with previous studies by either body wave tomography or surface wave tomography (Fan et al, 2015; He et al, 2017; Liu et al, 2018; Liu et al, 2014; Yao et al, 2010), and the other three WG's parameters are connected with velocity boundary and wave direction.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…According to the sensitivity kernel curve shown in Figure S5, the results of T = 20, 40, and 60 s are mostly sensitive to the structures at depth ranges of approximately 25, 60, and 90 km, respectively. The isotropic velocity maps of the southeastern Tibetan Plateau are consistent with previous studies by either body wave tomography or surface wave tomography (Fan et al, 2015; He et al, 2017; Liu et al, 2018; Liu et al, 2014; Yao et al, 2010), and the other three WG's parameters are connected with velocity boundary and wave direction.…”
Section: Resultssupporting
confidence: 90%
“…Journal of Geophysical Research: Solid Earth Liu et al, 2018;Liu et al, 2014;Yao et al, 2010), and the other three WG's parameters are connected with velocity boundary and wave direction.…”
Section: 1029/2019jb018395mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Pg tomography and the theory of maximum effective moment, Pei et al (2014) argued that this region is weak and ductile in nature and cannot accumulate stress to generate large (M > 7) earthquakes. Liu et al (2018) observed a LVL and a thick crust in this region; they associated the LVL with partial melt to account for the aseismic feature. Based on paleoseismic activity, Shao et al (2019) also concluded that rocks in this gap are ductile with low strength, although they found four paleoseismic events.…”
Section: Earthquake Focal Mechanisms Along Longmenshan Thrust Faultmentioning
confidence: 87%
“…Both the Wenchuan and Lushan earthquakes led to rich aftershock sequences. It is worth noting that there is a gap in aftershocks in a ∼60 km segment between the Wenchuan earthquake and the Lushan earthquake on the LFS, the potential seismic hazard of which has been debated (Liu et al., 2018; Pei et al., 2014).…”
Section: Introductionmentioning
confidence: 99%